Recent Advances in Radical Nitration Using tert-Butyl Nitrite - Song, Si-Zhe; Dong, Youren; Ge, Guo-Ping; Li, Qiang; Wei, Wen-Ting (Synthesis, 2020)
Nitro compounds serve as valuable intermediates for pharmaceuticals, agrochemicals, dyes, and polymers. In recent years, radical nitration using tert-butyl nitrite (t-BuONO) has attracted wide attention and desirable progress has been made. On the one hand, t-BuONO is a potential active nitro radical source and can react with various functional groups. On the other hand, as a green and novel nitration reagent, t-BuONO has relatively low price and can easily produce a radical under mild conditions, which undoubtedly provides a simple and efficient way for nitration reactions. To date, some important reviews are available that summarize the synthesis of nitro compounds. To the best of our knowledge, however, there is still no review that exclusively discusses the synthesis of nitro compounds using t-BuONO through a radical strategy. Therefore, this review aims to highlight the recent advances in radical nitration using t-BuONO as nitration reagent. The main progress in this area has been presented according to the type of reaction substrates. Special attention has been paid discussion of the reaction mechanisms and selected examples of substrates have been given. We hope this paper will be a useful reference and inspiration for those who are exploring the synthesis of nitro compounds using t-BuONO.1 Introduction2 Radical Nitration of Alkenes3 Radical Nitration of Aromatics4 Radical Nitration of Alkynes5 Radical Nitration of 1,n-Enynes6 Radical Nitration of Alkanes7 Summary and Perspective
Keywords: nitration; tert-butyl nitrite; radical reaction; C–N bond